Development and Validation of a Clinical Predictive Model for Identifying Hypertrophic Cardiomyopathy Patients at Risk for Atrial Fibrillation: The HCM-AF Score. (16th June 2021) - Carrick, Richard T.; Maron, Martin S.; Adler, Arnon; Wessler, Benjamin; Hoss, Sara; Chan, Raymond H.; Sridharan, Aadhavi; Huang, Dou; Cooper, Craig; Drummond, Jennifer; Rakowski, Harry; Maron, Barry J.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Atrial fibrillation (AF) is the most common sustained arrhythmia in hypertrophic cardiomyopathy (HCM), associated with impaired quality of life, risk for embolic stroke, and unpredictable onset. We sought to create a predictive model to identify risk for AF development in HCM. Methods: A cohort of 1900 patients with HCM followed for newly diagnosed AF in the Tufts HCM center was used for model development. A cohort of 387 patients from Toronto General Hospital was used for external validation. Data in the development cohort generated the HCM-AF score, a point score to predict AF probability at 2 and 5 years: left atrial dimension (+2 points per 6 mm increase), age at clinical evaluation (+3 points per 10-year increase), age at initial HCM diagnosis (−2 points per 10-year increase), and heart failure symptoms (+3 points if symptomatic). Results: The HCM-AF score stratifies risk as low (<1.0%/y; score ≤17), intermediate (1.0-2.0%/y; score 18 to 21), and high risk (>2.0%/y; score ≥22) for AF development for individual patients. Concordance of the HCM-AF score was 0.70 in the development cohort and 0.68 in the external validation cohort. In the development cohort, 17.2% of high-risk patients developed AF (rate 3.4%/y), while only 3.3% of low-risk patients developed AF (rate 0.7%/y) at 5 years ( P <0.001). Similarly, in the external validation cohort, 13.3% of high-risk patients developed AF (rate 2.7%/y), whereas only 1.1% of low-risk patients developed AF (rate 0.2%/y). The HCM-AF score provided greater predictive power for future AF risk than left atrial dimension alone (concordance of 0.58) and outperformed other non–HCM risk models. Conclusions: The HCM-AF score is a novel externally validated predictive tool to identify AF risk in HCM. This score can reliably stratify patients with HCM to risk of newly diagnosed AF and offers the opportunity to inform expectations regarding future clinical course.